System Thinkers: The Critical Role of Management Faculty in Advancing Student Understanding of Sustainability - Obeng, Hayford Asare; Boakye, Gilbert; Damalie , Elvis David; Arhinful, Richard (EduLine: Journal of Education and Learning Innovation, 2025)
This review emphasizes the crucial relationship between sustainable education and system thinking in the context of management faculty, underscoring the need for interdisciplinary collaboration and innovative teaching methods. The study explores how management educators help students gain a deeper grasp of social sustainability at a time when the G-20 is leading the charge to support global education sustainability. The paper emphasizes the critical role educators play in fostering a systemic viewpoint through an examination of successful educational tactics and practical implementations. The paper's focus on these essential components is in line with the G-20's objective of developing a generation that can effectively tackle intricate global issues.